2020
DOI: 10.1186/s11671-020-03380-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural-Dependent Photocatalytic Antibacterial Activity: a Case Study of Ag Modified BiVO4

Abstract: In this work, Ag/BiVO 4 heterostructural photocatalysts were developed in order to reveal exceptional structuraldependent photoinduced charge migration kinetics as well as the underlying photocatalytic antibacterial dynamic process. The structure-dependent interface of BiVO 4 and Ag nanoparticles was successfully constructed to improve the photoinduced interface charge transfer efficiency and interface correlation. DFT calculation indicated that a net charge of about 0.33 e between Ag and tz-BiVO 4 was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…3d), the binding energies ranging from 528 eV to 535 eV can be deconvoluted into three subpeaks at 529.8 eV, 531.1 eV and 532.6 eV, which can be assigned to lattice oxygen, oxygen vacancies and adsorbed oxygen, respectively. 43 In the Ag 3d spectral region (Fig. 3e), two major peaks centered at 368.0 and 374.0 eV are related to the Ag 3d 5/2 and Ag 3d 3/2 spin orbitals of metallic Ag, 44 which is consistent with the HRTEM image results.…”
Section: Resultssupporting
confidence: 84%
“…3d), the binding energies ranging from 528 eV to 535 eV can be deconvoluted into three subpeaks at 529.8 eV, 531.1 eV and 532.6 eV, which can be assigned to lattice oxygen, oxygen vacancies and adsorbed oxygen, respectively. 43 In the Ag 3d spectral region (Fig. 3e), two major peaks centered at 368.0 and 374.0 eV are related to the Ag 3d 5/2 and Ag 3d 3/2 spin orbitals of metallic Ag, 44 which is consistent with the HRTEM image results.…”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, all the Ag loaded photoanodes gave better photocurrent response and the highest response was 0.58 mA cm −2 . This observation clearly affirmed that as a noble metal, Ag could act as a photosensitizer absorbing photons and regulating the generation of charge carrier through direct electron transfer or dipole–dipole coupling connection 31 , 41 . Additionally, the behaviour of the electrodes with different bias potential was also examined through LSV with light on/off and it was observed that the magnitude of the transient photocurrent response increased with the applied potential (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, noble metals can act as photosensitizers promoting the absorption of visible light. Additionally, noble metals can form Schottky barrier when in contact with semiconductors when the electrons from the interface of the semiconductor move towards the noble metal 30 , 31 . This largely promote the separation of photogenerated charge carriers because electrons from the conduction band of the semiconductors can easily migrate to the conduction levels of the noble metals.…”
Section: Introductionmentioning
confidence: 99%